Anaerobic digestion of tomato processing waste: Effect of alkaline pretreatment. (1st November 2015) - Calabrò, Paolo S.; Greco, Rosa; Evangelou, Alexandros; Komilis, Dimitrios
Abstract: The objective of the work was to assess the effect of mild alkaline pretreatment on the anaerobic biodegradability of tomato processing waste (TPW). Experiments were carried out in duplicate BMP bottles using a pretreatment contact time of 4 and 24 h and a 1% and 5% NaOH dosage. The cumulative methane production during a 30 d period was recorded and modelled. The alkaline pretreatment did not significantly affect methane production in any of the treatments in comparison to the control. The average methane production for all runs was 320 NmL/gVS. Based on first order kinetic modelling, the alkaline pretreatment was found to slow down the rate of methanogenesis, mainly in the two reactors with the highest NaOH dosage. The biodegradability of the substrates ranged from 0.75 to 0.82 and from 0.66 to 0.72 based on two different approaches. Highlights: We studied alkaline pretreatment prior to the anaerobic digestion of tomato waste. Four treatments with different alkali dosages and contact times were used. None of the pretreatments affected methane yields in comparison to the control. Alkaline pretreatment resulted in the reduction of methane generation rates.